Treatment planning systems dosimetry auditing project in Portugal - Lopes, MC (2014)
BACKGROUND AND PURPOSE: The Medical Physics Division of the Portuguese Physics Society (DFM_SPF) in collaboration with the IAEA, carried out a national auditing project in radiotherapy, between September 2011 and April 2012. The objective of this audit was to ensure the optimal usage of treatment planning systems. The national results are presented in this paper. MATERIAL AND METHODS: The audit methodology simulated all steps of external beam radiotherapy workflow, from image acquisition to treatment planning and dose delivery. A thorax CIRS phantom lend by IAEA was used in 8 planning test-cases for photon beams corresponding to 15 measuring points (33 point dose results, including individual fields in multi-field test cases and 5 sum results) in different phantom materials covering a set of typical clinical delivery techniques in 3D Conformal Radiotherapy. RESULTS: All 24 radiotherapy centers in Portugal have participated. 50 photon beams with energies 4-18 MV have been audited using 25 linear accelerators and 32 calculation algorithms. In general a very good consistency was observed for the same type of algorithm in all centres and for each beam quality. CONCLUSIONS: The overall results confirmed that the national status of TPS calculations and dose delivery for 3D conformal radiotherapy is generally acceptable with no major causes for concern. This project contributed to the strengthening of the cooperation between the centres and professionals, paving the way to further national collaborations.